Risk Assessment of International Seabed Mining Implementing the Analytic Hierarchy Process - Xinyu Ma; Yejian Wang; Kehong Yang; Jinrong Li; Yan Li; Dongsheng Zhang; Rong Wang; Yinxia Fang (Journal of Marine Science and Engineering, 2025)
The international seabed area (“the Area”) harbors abundant metal mineral resources that are critical to address global metal supply–demand and sustainable development. However, exploitation of mineral resources in the Area faces complex risks spanning politics, economy, technology, science, environment, society, industry, and law. No commercial-scale deep-sea mining operations have been conducted to date. Systematic risk identification and prioritization can inform strategic planning for stakeholders. This study employs literature analysis and an 80-expert questionnaire to identify key risk factors affecting mineral exploitation in the Area. Using the Analytic Hierarchy Process (AHP), we quantitatively assess the relative importance and weightings of these risks. Our results indicate that Level 1 risk groups prioritize (1) policy and public opinion risk, (2) extended continental shelf (ECS) delineation risk, (3) high sea marine protected areas (HSMPAs) establishment risk, and (4) mining area economic value risk. The five most critical Level 2 risk factors are (i) policy changes in contractor states, (ii) ECS-mining area boundary conflicts, (iii) environmental provisions in exploitation regulations at the international seabed (ER), (iv) ER implementation delays, and (v) mineral resource uncertainty. These findings provide actionable insights for contractors, policymakers, and stakeholders to optimize decision making in deep-sea mining projects.

Internal Tide Generation and Propagation in the Sulu Sea Under the Influence of Circulation - Yuhao Rong; Yunchao Yang; Chao Wang; Heng Li; Jiahui Li; Xiaodong Huang (Journal of Marine Science and Engineering, 2025)
The Sulu Sea has active internal tides (ITs) and basin-scale circulation. This study, for the first time, employs three-dimensional simulations to investigate the effects of the Sulu Sea circulation on IT generation and propagation. Results reveal that the cyclonic circulation can enhance the semi-diurnal and diurnal IT energy conversion in the Sulu Archipelago by approximately 17% and 77%, respectively, compared to those without circulation for semi-diurnal ITs (4.36 GW) and diurnal ITs (2.76 GW). This different increase portion between semi-diurnal and diurnal ITs is attributed to different influences of circulation on the positive and negative conversion rates for semi-diurnal and diurnal ITs. Energy budget analysis indicates that circulation increases the proportion of dissipation near source regions from 88% (90%) to 94% (93%) and reduces the proportion of energy flux radiation from 12% (10%) to 6% (7%) for semi-diurnal (diurnal) ITs. The ray-tracing results indicate that the cyclonic circulation induces significant westward refraction of IT rays by modulating IT speeds in counter-current/co-current regions. Further sensitive experiments reveal that circulation-induced stratification weakens the refraction, whereas the background currents strengthen it, with the latter dominating. These findings advance our understanding of the IT behaviors in the Sulu Sea under the modulation of circulation.

Experimental and Numerical Study of Suspended Inter-Array Cable Configurations for Floating Offshore Wind Farm - Di-Rong Li; Yu-Shiou Su; Ray-Yeng Yang (Journal of Marine Science and Engineering, 2024)
The present study evaluates the feasibility of using a fully suspended inter-array cable system for an offshore wind farm. It includes both numerical simulations and a scaled-down experiment, conducted at a 1:49 scale, to validate the numerical results. To achieve the goal, a 15 MW floating offshore wind turbine (FOWT) and a floating offshore substation (FOSS) are involved to simulate the wind farm array. This study incorporates the 50-year return period conditions of the Taiwan Hsinchu offshore area, which has a water depth of about 100 m, to validate the specifications related to the platform motion and mooring line tension. Additionally, an analysis of the tension, curvature, and fatigue damage of the dynamic cable system is discussed in this research. Because a fully suspended cable is a relatively new concept and may be more frequently considered in a deeper water depth area, numerical simulation software Orcina Orcaflex 11.4 has been chosen to conduct the fully coupled simulation, determining whether the fully suspended cable system could effectively withstand the challenges posed by extreme sea conditions. This is due to the reason that a fully suspended cable would occupy a larger space in the ocean, which may pose a risk by influencing the navigation of the vessels. Therefore, the cable laying depth under normal sea states is also discussed to evaluate the influence over vessel navigation. This study also collects the long-term environmental data from the Central Weather Bureau, Taiwan, to calculate the accumulative cable fatigue damage under different sea states. To integrate the results, this research applies fitness parameters to evaluate the feasibility of each cable configuration. Covering the cable performance under extreme sea states and regular operating sea states offers valuable insights for applications in ocean engineering.